The Influence of Work-Life Balance, Transformational Leadership Style, and Work Stress on Job Satisfaction of Employees at the Ternate City KPU Secretariat - M. Arfan Ramli; Ahmad Yani Abdurrahman; Zulkifli Zulkifli (Green Publisher Indonesia, 2026)
This study aims to analyze the influence of work-life balance, transformational leadership style, and job stress on the job satisfaction of employees at the Secretariat of the General Elections Commission (KPU) of Ternate City. The background of this research is based on the phenomenon of imbalance between work and personal life, shifts in leadership styles that affect employee comfort, and increased job stress among employees due to workload and pressure during election stages. This research employs a quantitative approach with an associative research type. The population of the study consists of all 32 employees of the KPU Secretariat in Ternate City, and the entire population was used as the sample (saturated sampling). Data collection was conducted through questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. The results show that partially, work-life balance and transformational leadership style have a positive and significant effect on job satisfaction, while job stress has a negative and significant effect on job satisfaction. Simultaneously, all three variables significantly influence job satisfaction. These findings highlight the importance of time management, inspirational leadership, and stress management in improving employee job satisfaction, especially in public organizations with high workloads such as the KPU. This study is expected to contribute to organizational policy-making in creating a healthy, productive, and sustainable work environment.